Analysis of Speech, Context, and Multimodality in Corruption Prevention Poster on Instagram Social Media - Ina; Fauzi, Aziz; Achmad Prasetyo; Aisha Nadya (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research departs from the problem of the rampant practice of corruption that is normalized in social and bureaucratic life, as well as the need for effective critical communication strategies in the digital space to build anti-corruption awareness. The purpose of this study is to describe the types and functions of directive speech, the role of social context, and the contribution of multimodal elements in corruption prevention posters. This study uses a descriptive qualitative method with a multimodal pragmatic approach. The research data is in the form of 23 posters of corruption prevention campaigns. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn, by combining pragmatic analysis to identify directive speech actions and multimodal analysis to interpret the interaction between text and visual elements. The results showed that the posters were divided into three main categories, namely rejecting bribes, rejecting gratuities, and rejecting illegal levies and extortion, all of which were dominated by directive speech with the functions of commanding, prohibiting, and giving warnings. Multimodal elements such as colors, symbols, gestures, character expressions, and visual layouts have been proven to strengthen speech illusion and build a stronger persuasive effect. The conclusion of this study shows that the multimodal pragmatic approach is able to comprehensively reveal how language, context, and visuals interact with each other in building critical, persuasive, and ideological anti-corruption communication strategies in digital public spaces.